Design and Optimization of Automated Storage and Retrieval Systems: A Review - Cinar, Zeki Murat; Zeeshan, Qasim (Springer International Publishing Ag, 2022)
Automated Storage and Retrieval Systems (AS/RS) are warehouses, specifically designed for material handling in modern manufacturing systems and are extensively utilized as distribution centers, due to the advantages of improved inventory control, cost-effective utilization of time, space and equipment. With the advent of smart manufacturing in the Industry 4.0 era, the significance of adopting automation technology in warehousing becomes increasingly imminent. Techniques and tools are being developed to manage, control, design, and optimize the AS/RS(s). Over the years, many researchers have focused on the design, analysis, and optimization of various AS/RS configurations. This paper aims to present a systematic literature review on the research in Configuration design and Optimization of AS/RS, by classifying the research according to the design objectives, configurations and optimization algorithms used, in order to highlight and expand the awareness on the current best practices, progress, and future research directions.
Global Joint Conference on Industrial Engineering and Its Application Areas (GJCIE) -- AUG 14-15, 2020 -- ELECTR NETWORK
Keywords: Automated storage and retrieval systems; Configuration design; Optimization; Warehouse